The Analysis of the Integration of Halal Concepts in the Science Curriculum and Teaching: A Case Study at Al Kamal NW Narmada Islamic Junior and Senior High Schools - Al Farisi, Salman; Kurnia, Nova; Sukri, Akhmad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study examined the potential integration of halal concepts into the science curriculum and teacher-reported instructional practices at SMP and SMA Islam Al Kamal NW Narmada. Using an embedded qualitative case-study design, the study combined researcher-developed curriculum mapping with written responses from four purposively selected science teachers representing integrated science, Biology, Chemistry, and Physics. Data were analysed through qualitative content analysis, thematic coding, and cross-source comparison. The findings identified the strongest opportunities for integration in topics related to material sources, food and nutrition, the digestive system, food additives, product composition, microorganisms, fermentation, biotechnology, health, and production processes. Teachers also identified additional links through acids and bases, solutions, colloids, carbon compounds, quantities, measurement, and product observation. Reported practices included presenting examples of halal and non-halal products, examining labels and ingredient lists, observing products available in the community, and conducting simple practical activities such as pH testing. However, the reported implementation remained largely contextual and did not yet demonstrate systematic engagement with evidence evaluation, uncertainty, argumentation, or socioscientific decision-making. The study also highlights the need to distinguish scientific analysis from formal halal determination, as laboratory evidence alone cannot establish halal status without traceability, process documentation, and authorised certification. Overall, halal concepts offer a relevant interdisciplinary and socioscientific context for science learning, provided that integration is conceptually accurate, pedagogically structured, and supported by appropriate resources, teacher professional development, and collaboration with Islamic Education teachers. Further research should include classroom observations and direct assessment of student learning outcomes across diverse Islamic secondary school contexts.